Retinitis pigmentosa: Advances in gene and retinal therapy (Research, Society and Development, 2025)
Retinitis pigmentosa is a heterogeneous group of inherited retinal dystrophies characterized by progressive degeneration of photoreceptors, resulting in gradual vision loss and significant impairment of quality of life. Advances in the genetic and molecular understanding of the disease have driven the development of innovative therapeutic strategies, particularly gene therapy and other emerging retinal approaches. The objective of this study was to analyze, through a narrative literature review, the main advances in gene therapy and retinal therapies applied to retinitis pigmentosa, emphasizing their mechanisms of action, clinical results, limitations, and future perspectives. The methodology included the analysis of experimental and clinical studies published in relevant scientific databases, addressing interventions such as gene replacement and editing, stem cell use, optogenetics, and retinal prostheses. The results demonstrate that gene therapy offers significant benefits in specific subgroups of patients, especially in stabilizing disease progression and improving visual function. Retinal therapies, in turn, show potential for partially restoring visual function in advanced stages, although with still heterogeneous results. It is concluded that these therapeutic advances represent a paradigm shift in the management of retinitis pigmentosa; however, the widespread clinical application of these strategies depends on overcoming technical, economic, and access challenges, as well as the continuation of translational research.